(untitled) (CIPEEX, 2024)
THE TECHNICAL VISITS PROVIDE AN OPPORTUNITY TO GAIN MORE PRACTICAL KNOWLEDGE IN VARIOUS AREAS, OFFERING EXPERIENCES BEYOND THEORETICAL ACTIVITIES. ON OCTOBER 1, 2022, STUDENTS FROM THE BUSINESS ADMINISTRATION COURSE AT THE EVANGELICAL UNIVERSITY OF GOIÁS - CAMPUS CERES PARTICIPATED IN A VISIT WHERE THEY LEARNED ABOUT THE PRODUCTION PROCESS OF DRY, WET FOOD, AND SNACKS FOR ANIMALS AT AN INDUSTRY. THE MAIN OBJECTIVE WAS TO REPORT ON THIS EXPERIENCE AND CONNECT IT WITH THE THEORETICAL CONTENT TAUGHT IN CLASS. UPON ENTERING THE FACTORY FACILITIES, THE HISTORY, MISSION, VISION, AND VALUES OF THE COMPANY WERE PRESENTED, ALONG WITH THE PRODUCT PORTFOLIO, STAGES OF THE PROCESS, AND ORGANIZATIONAL OBJECTIVES. STUDENTS WERE THEN TRAINED ON THE USE OF PERSONAL PROTECTIVE EQUIPMENT REQUIRED BY REGULATORY STANDARD NR 06 TO ACCESS DIFFERENT AREAS OF THE INDUSTRY. THEY WERE INTRODUCED TO THE PRODUCTION PROCESS, STARTING FROM THE RECEIPT OF RAW MATERIALS AND MOVING ON TO MACHINERY SUCH AS EXTRUDERS, DRYERS, COOLERS, AND FINALLY, PRODUCT FILLING AND STORAGE. THROUGHOUT THE PRESENTATION, THE IMPORTANCE OF IMPLEMENTING TOTAL QUALITY PHILOSOPHY TO ACHIEVE EXCELLENCE IN PRODUCT PRODUCTION WAS EMPHASIZED. THE INDUSTRY ADOPTS A JUST-IN-TIME PRODUCTION MANAGEMENT SYSTEM TO MANAGE PURCHASES, PRODUCTION, AND SALES, MINIMIZING WASTE DURING SEASONAL PERIODS. ADDITIONALLY, THE COMPANY EMBRACES THE ESG (ENVIRONMENTAL, SOCIAL, AND GOVERNANCE) APPROACH, FOCUSING ON SOCIAL GOALS AND NOT JUST PROFIT MAXIMIZATION. FROM THIS EXPERIENCE, IT IS EVIDENT THAT TOTAL QUALITY IS IMPORTANT FOR CONSIDERING ENVIRONMENTAL ISSUES AND AVOIDING THE DEPLETION OF NATURAL RESOURCES. HENCE, PET INDUSTRY QUALITY CONTROL IS AS STRINGENT AS THAT OF THE HUMAN FOOD INDUSTRY.